(untitled) (Heritage, 2025)
Football, as a very popular sport in Yugoslavia, also found its admirers in the towns of Morava Banovina. The Niš Football Association, founded in 1931, gathered football clubs from the territories of Niš, Kruševac, Knjaževac, Zaječar, Negotin and Bor, while the clubs from Jagodina, Ćuprija, Paraćin, Svilajnac and Kraljevo were part of the Kragujevac Football Association. The main problem faced by this sport was the lack of finances and adequate fields. Although, as sports societies, the clubs collected membership fees and donations, the insufficient flow of money led many to turn to the competent Ministry of Physical Education for help. Although the ministry allocated annual subsidies, more visible progress in terms of the development of this sport was not achieved. The state’s concern for the development of football was reflected in the increased control of the clubs themselves, due to the fear of negative propaganda, especially communist propaganda. In addition, every international match, primarily against clubs from Romania and Bulgaria, meant, for the purpose of security checks, the activation of the Ministries of Foreign and Internal Affairs.